Predicting Purchase Decisions on Kediri Consumer Students using Shopee Application - Diana Ambarwati -; Rike Selviasari; Anita Sumelvia Dewi (Asian Journal of Management, Entrepreneurship and Social Science, 2022)
This study predicts the effect of promotion giving and pricing on brand image. In addition, to predict the effect of promotion giving and pricing on purchase decisions. And also predicts the effect of promotion giving and pricing on purchase decisions through the Shopee brand image on students in Kediri. This research uses a quantitative approach with research data sources obtained from primary and secondary data. The data collection technique by distributing questionnaires using Smart PLS analysis. This study uses purposive sampling with a sample of 100 students with the criteria of being domiciled in Kediri. Respondents have made purchases of goods at Shopee more than two times and are 20 years old. The results found promotion giving and pricing have a direct and positive effect on Shopee's brand image. However, promotion giving and pricing have no direct and significant negative effect on Shopee consumer purchases. In this study, brand image plays an essential role in mediating. Brand image has an indirect positive effect on purchase decisions. Proves that Shopee's good brand image of the public is not only promotion giving and pricing. Other variables influence the purchase decision of Shopee consumers outside of this research.